Welfare State Regimes and Mothers' Poverty - Karen Christopher (Luxembourg Income Study (LIS), 2001)
In this paper I assess the extent to which welfare states reduce poverty among single mothers and all mothers. I focus on two different typologies of welfare states. One identifies the gendered assumptions underlying social policies, while the other focuses on how welfare states and labor markets affect class inequality. Using data from the Luxembourg Income Study, I show how tax and transfer systems and employment supports in nine Western nations affect the poverty rates of single mothers and all mothers vis-à-vis other groups. I find that particularly in the Scandinavian nations, and to a lesser extent in France, the Netherlands and U.K., the tax and transfer system, employment supports, or a combination of the two allow most single mothers to form autonomous households that escape poverty. I conclude by discussing how my findings speak to the different typologies of welfare state regimes.
Keywords: 330; Alleinerziehende; Familienleistungsausgleich; Armutsbekämpfung; Weibliche Arbeitskräfte; EU-Staaten; Kanada; USA